Serpentine retinal pigment epithelial tear - Aditya Maitray; Piyush Kohli; Naresh Babu (Taiwan Journal of Ophthalmology, 2021)
We report a case of retinal pigment epithelial tear in a patient with peripheral exudative hemorrhagic chorioretinopathy (PEHCR). A 60-year-old diabetic female presented with left eye metamorphopsia. Fundus examination showed bilateral peripheral retinal pigment epithelium (RPE) degeneration, and a large serpentine-shaped RPE degeneration tract extending from the superotemporal arcade to the inferior periphery with associated subretinal hemorrhages in her left eye. This tract curved around the fovea, just sparing it. Fundus fluorescein and indocyanine green angiographies showed bilateral polyps in the superotemporal periphery. Optical coherence tomography through the tract showed scrolled up RPE at its edges with bare underlying Bruch's membrane and choroid in the region of the rip. There was no sign of an underlying pigment epithelial detachment. The patients with PEHCR should be prognosticated about such a rare vision-threatening macular complication.